Pengaruh Kebijakan Bebas Visa Kunjungan Singkat Terhadap Kasus Penyelundupan Narkoba di Indonesia Tahun 2016-2018 - Mukti, Rahardian Krishna; Pattipeilohy, Shary Charlotte Henriette (Journal of International Relations, 2020)
The Indonesian Government has had a drug problem since the Dutch colonial era. This is a legacy that is currently still a problem in the handling, eradication and prevention of drugs in Indonesia. On the other hand, the Government of Indonesia has a Visa Free Short Visit policy for 169 countries. The policy was formed with the aim of increasing economic foreign exchange through the tourism sector. However, this policy actually has an impact on increasing the number of drug smuggling cases committed by foreign nationals in Indonesia. This study aims to explain how the effect of Visa-Free Short Visit on drug smuggling in Indonesia, using qualitative research methods with secondary data sources. In analyzing Visa-Free Short Visit, this study uses the theory of globalization and transnationalism. The theory of globalization and transnationalism will analyze and explain that the openness of the state can affect the risk of state security. This research ultimately reveals that the Visa Free Short Visit to 169 countries has vulnerabilities to state security such as drug smuggling problems so that this policy needs further evaluation.